Linear induction accelerator with charge and current compensation - Karas', V.I.; Kornilov, E.A.; Shulika, O.N. (Вопросы атомной науки и техники, 2001)
The research of inertial controlled fusion (ICF) on high-current heavy-ion beams is one of the main trends in ICF. Modern techniques of a heavy-ion beam production and acceleration make it possible to obtain high-current beams with high intensity using linear induction accelerators (linacs). ICF purposes require the increasing of the beam intensity and the beam brightness by several orders. The main process that restricts the high-current ion beam intensity is the beam spreading caused by the influence of self-fields of charged particle beam. Self-fields are several orders greater than the external fields used for beam control, acceleration and focusing. Under these conditions, it is impossible to obtain high-current heavy-ion beams of quality necessary for ICF without charge and current compensation of beams.